Analyses of factors affecting and predicting the efficacy of tacrolimus in patients with idiopathic membranous nephropathy - Zhang Cheng-ning; Duan Su-yan; Yuan Yang-gang; Zhu Jing-feng; Huang Zhi-min; Sun Bin; Zhang Bo; Mao Hui-juan; Xing Chang-ying (Linchuang shenzangbing zazhi)
ObjectiveTo explore the factors of affecting and predicting the therapeutic efficacy of tacrolimus （FK506） in patients with idiopathic membranous nephropathy （IMN）.MethodsA total of 76 IMN patients receiving oral FK506 （0.05-0.075 mg·kg-1·d-1） plus prednisone （0.5 mg·kg-1·d-1） were recruited. Clinical characteristics， pathological indicators， therapeutic effect and adverse reactions were recorded at baseline and during 24-week treatment. According to curative effect， they were divided into three groups of complete remission （CR）， partial remission （PR） and no remission （NR）. The impact of clinical characteristics on efficacy and outcome was examined.ResultsNo difference existed in average blood trough concentration of tacrolimus among three groups. There was no correlation between blood trough concentration and remission rate. The remission rate in trough concentration range of 4-6 μg/L was higher than other concentration ranges. The remission rate was lower in males than that in females. Baseline serum creatinine was significantly lower in CR/PR group than that in NR group ［（69.18±13.61）μmol/L、（80.20±16.44）μmol/L vs （92.53±22.60）μmol/L，P<0.05］； eGFR was significantly higher in CR/PR group than that in NR group ［（95.89±16.46）mL·min-1·（1.73 m2）-1、（96.96±17.01）mL·min-1·（1.73 m2）-1 vs （78.70±20.01）mL·min-1·（1.73 m2）-1，P<0.05］； serum uric acid was significantly lower in CR group than that in PR/NR group ［（344.79±81.85）μmol/L vs （405.72±89.77）μmol/L、（382.48±96.32）μmol/L］； tubular atrophy （TA） was significantly lower in CR group than that in PR/NR group （1 vs 18、10，P<0.01）. Multivariate COX regression analysis indicated that eGFR and serum albumin were independent factors for predicting the efficacy of tacrolimus in IMN patients.ConclusionMale， baseline creatinine， eGFR and TA are four key influencing factors of efficacy. And eGFR and serum albumin are independent predictive factors of outcomes.